Analisis Determinan Minat Mahasiswa Akuntansi Berkarier Sebagai Akuntan Publik - Fadhilla Maulidina Rabia; Nora Hilmia Primasari (SUBSTANSI, 2021)
This study aims to analyze the effect of financial rewards, motivation, work environment, labor market considerations, and adversity intelligence on the interest of accounting students to have a career as public accountants. The population in this study were accounting students at Universitas Budi Luhur. Determination of the sample using purposive sampling technique. The data processing of this research uses multiple linear regression method. The results of this study indicate that financial rewards, motivation, and adversity intelligence have a positive effect on the interest of accounting students to have a career as public accountants, while the work environment and labor market considerations have no effect on the interest of accounting students to have a career as public accountants.